A Framework for Omnichannel Differentiation Strategy. Integrating the Information Delivery and Product Fulfillment Requirements. - Kassim, Erne Suzila; Hussin, Husnayati (Springer Nature, 2019)
Technology and innovation have the capability to change the many aspects of business for good and bad. With technology capabilities, customers are demanding for better products and service delivery anytime, anywhere. Thus, companies and retailers are driven to the new model of business, omnichannel. However, delivering an omnichannel solution is a challenging effort. It requires unique strategies for implementation success. In this chapter, we present the experience of a card design and printing company in their journey to an omnichannel business. Two main questions are addressed: how does information delivery and product fulfillment fit the information-fulfillment matrix and what is the formula for omnichannel differentiation strategies. While the practices fit into the four components of the matrix, the major implementation is on the offline information-store pickup and online information-store pickup quadrants. In addition, the four major omnichannel strategies adopted for business continuity management are managing a good customer relationship, aligning knowledge and technology to the current trend, retaining customer trust and having a strict policy on security and data confidentiality. In essence, omnichannel requires a harmonious integration of people-technology-organization for its sustainability. Based on the case, we provide suggestions to guide organizations with similar plans, and the implications for the industry and body of knowledge.